Strain Engineering for High-Performance Phase Change Memristors - Hou, Wenhui; Azizimanesh, Ahmad; Dey, Aditya; Yang, Yufeng; Wang, Wuxiucheng; Chen, Shao; Wu, Hui; Askari, Hesam; Singh, Sobhit; Wu, Stephen M (arXiv.org, 2023)
A new mechanism for memristive switching in 2D materials is through electric-field controllable electronic/structural phase transitions, but these devices have not outperformed status quo 2D memristors. Here, we report a high-performance bipolar phase change memristor from strain engineered multilayer 1T'-MoTe\(_{2}\) that now surpasses the performance metrics (on/off ratio, switching voltage, switching speed) of all 2D memristive devices, achieved without forming steps. Using process-induced strain engineering, we directly pattern stressed metallic contacts to induce a semimetallic to semiconducting phase transition in MoTe2 forming a self-aligned vertical transport memristor with semiconducting MoTe\(_{2}\) as the active region. These devices utilize strain to bring them closer to the phase transition boundary and achieve ultra-low ~90 mV switching voltage, ultra-high ~10\(^8\) on/off ratio, 5 ns switching, and retention of over 10\(^5\) s. Engineered tunability of the device switching voltage and on/off ratio is also achieved by varying the single process parameter of contact metal film force (film stress \(×\) film thickness).